2009
DOI: 10.1111/j.1479-828x.2009.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in overactive bladder syndrome after polypropylene mesh surgery for cystocele

Abstract: Our study confirmed the efficacy of the propylene mesh introduction surgery for cystocele for the improvement of OABS symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
3
12
0
1
Order By: Relevance
“…Anatomic cure rate was 95.8% at 1 year, and symptom scores showed significant improvement in the combined OAB symptom score, specifically in urgency, daytime frequency, and incontinence. There was also a significant increase in maximum flow rate, from 9.2 to 15.0 mL/s, to which the authors attributed much of the subjective improvement [35]. The Prolift system was also studied in 121 patients in a multi-institutional trial in Scandinavia.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 95%
See 1 more Smart Citation
“…Anatomic cure rate was 95.8% at 1 year, and symptom scores showed significant improvement in the combined OAB symptom score, specifically in urgency, daytime frequency, and incontinence. There was also a significant increase in maximum flow rate, from 9.2 to 15.0 mL/s, to which the authors attributed much of the subjective improvement [35]. The Prolift system was also studied in 121 patients in a multi-institutional trial in Scandinavia.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 95%
“…Okui et al [35] carried out a study of the Gynecare Prolift (Ethicon, Somerville, NJ) four-point transobturator mesh anterior repair in 20 patients with grade 2 or 3 POP and OAB syndrome on questionnaire, and compared these with 18 conservatively managed controls. Anatomic cure rate was 95.8% at 1 year, and symptom scores showed significant improvement in the combined OAB symptom score, specifically in urgency, daytime frequency, and incontinence.…”
Section: Surgical Repair Of Pelvic Organ Prolapsementioning
confidence: 98%
“…Therefore, a direct comparison between that study and ours is problematic. Okui et al [22] conducted a study to observe the improvements in the overactive bladder syndrome after cystocele repair. In that study, the anatomical success rate was similar to ours, and the UDI scores showed significant improvement 1 year postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Paraiso was the only one to report a pelvic abscess after surgery [5]. In 11 non-randomized studies (623 patients), nine of which using NAS meshes, no post-surgical infection was detected [33,[36][37][38][39][40][41][42][43][44][45]. Six studies with NAS meshes reported post-surgical hyperthermia, meaning 3.15% out of 755 cases [46][47][48][49][50][51].…”
Section: Infectionmentioning
confidence: 99%